Determinants of user satisfaction and usage intention of e-Filing system in Malaysia / Ashameena Nagaratnam - Ashameena , Nagaratnam (2021)
Purpose – The purpose of this paper is to investigate on the factors that affect the user to filing corporate tax returns using the e-filing system in Malaysia. Design/methodology/approach – The study uses quantitative research approach where questionnaires with close-ended questions were used. In total, 200 questionnaires were distributed and 187 were found usable for data analysis. Analysis of data was done through two types of statistical analysis software which are SPSS and Smart PLS. Structural equation modelling is used to analyse the hypotheses. 11 hypotheses were formulated and tested. Findings – The results shows that service quality and user satisfaction have significant impact on usage intention while trust in technology significantly influenced perceived risk among users.Meanwhile, information quality and trust in government significantly influenced user satisfaction.Based on the three dimensions of IS success model, service quality and information quality were found to have the most consistent and significant influence over user satisfaction and usage intention in adopting the system. The implications are further discussed. Originality/value – This study proposes a framework which constitutes the combination of Information System Success Model (ISSM) theory and Trust theory. This framework is useful since it is able to identify factors that affect users’ adoption of e-filing system.